Growth Performance, Feed Efficiency and Ingestive Behavior of Sahiwal Calves Divergently Selected for Residual Feed Intake - Singh, Anil Kumar; Kumar, Muneendra; Kumar, Vinod; Roy, Debashis; Kushwaha, Raju; Vaswani, Shalini; Kumar, Avinash (Indian Journal of Animal Nutrition, 2019)
This study aimed to evaluate differences in performance, feed utilization efficiency, and ingestive behavior between low and high residual feed intake (RFI) growing cattle. Eighteen growing female Sahiwal calves (age 10Â±4 months, body weight 100Â±45 kg) were fed individually using ad libitum feeding of total mixed ration for a period of 90 days. RFI varied from -0.53 to 0.40 kg dry matter (DM)/day with a mean RFI of -0.27 to 0.17 kg DM/day in low and high RFI calves, respectively. Significant (P